CRM- A New Dimension of Marketing - Saraswathy, B. C. (Indian Journal of Marketing, 2006)
Customer Relationship Management/Customer Relationship Marketing (CRM) has today become a typical marketing strategy in the milieu of changed customer behaviour. Of late, customers have become smarter and have all the information at their fingertips with internet explosion and communication revolution. They have become more cost driven, value conscious and are approached by a legion of competitors with equal or better offers. It has also dawn on companies that retaining a customer is much less expensive than attracting a new customer. Accordingly, marketing practices have shifted from basic marketing to reactive marketing and then to relationship marketing. Companies have started to align their processes and practices around the customers as well as the product. CRM is, thus, the process of building profitable, long-term relationships with customers by fostering repeated purchases. For its successful implementation, CRM should be seen as a philosophy cutting across the organization rather than a mere short-term marketing tool to boost sales.